Tailoring depolarization temperature by phase transition causing properties evolution in Bi0.5(Na1-xKx)0.5TiO3 ceramics. (1st July 2022) - Yang, Diyan; Han, Jihui; Yin, Jie; Xue, Haoyue; Wu, Jiagang
Highlights: K/Na ratio can regulate t d (from 90 °C to 246 °C) of Bi0.5 (Na1- x K x )0.5 TiO3 ceramics. T d defers with the increase of the ratio of P 4 mm/P 4 bm, and the structural transition from short-range-correlated P 4 bm to long-range-correlated P 4 mm should be the driving force for the growth of poling-induced domain size. A small amount of k doping destabilizes ferroelectric long-range order, while with an increment of k substitution, ferroelectric long-range order becomes stabilized. Abstract: (Bi0.5 Na0.5 )TiO3 -based materials have attracted widespread attention due to large electro-strain, large remnant polarization ( P r ) and high Curie temperature ( T C ), but the existence of inherent depolarization temperature ( T d ) limits the temperature stability and application temperature range. In this work, we find that K/Na ratio can regulate T d (from 90 °C to 246 °C) of the ceramics, which confirms that the increase of K substitution can effectively improve the temperature stability of the material. The phase structure and electrical properties of Bi0.5 (Na1- x K x )0.5 TiO3 (BNKT x ) ceramics can be well modulated by changing K/Na. In addition, BNKT x system exhibits excellent piezoelectric response at morphotropic phase boundary (MPB) of 20% BKT content ( d 33 =180 pC/N), where rhombohedral ( R 3 c ) phase and tetragonal ( P 4 bm ) phase coexist in MPB. With K further substitution, BNKT x ceramics transform into tetragonal phase, and the domain size grows due to the structural transition from short-range-correlated P 4 bm to long-range-correlated P 4 mm . The deferment of T d is also tightly related to the increase of P 4 mm/P 4 bm ratio. This work can provide an effective way to tailor depolarization temperature and electrical properties of BNT-based ceramics.